Lokalitas Arsitektur Tradisional Bali dan Konsep Tri Hita Karana Pada Gereja Katolik Paroki Roh Kudus Katedral Denpasar Pasca Renovasi - Desy Yuliastuti Ida Ayu Made; Ikaputra (Jurnal Anala, 2025)
Balinese Traditional Architecture is a cultural heritage that has developed from generation to generation and is built based on traditional rules, both written and oral. One of the main concepts in this architecture is Tri Hita Karana, which means "three causes of happiness." This concept reflects the balance of relationships between humans and God (Parahyangan), humans and fellow humans (Pawongan), and humans and the environment (Palemahan). In its application, the Tri Hita Karana concept is also associated with Tri Mandala and Sanga Mandala, which regulate spatial division and building orientation according to the philosophy of Balinese traditional architecture. Bali is known as an island with a high level of religious tolerance. The significant presence of Catholics in Bali has led to the establishment of various churches, including Gereja Katolik Paroki Roh Kudus Katedral Denpasar. This church incorporates Gothic architectural style combined with elements of traditional Balinese architecture, as seen in its facade and materials used. This study aims to: (1) identify the factors influencing the application of Tri Hita Karana in the architecture of Gereja Katolik Paroki Roh Kudus Katedral Denpasar and (2) analyze the localization of the church before and after renovation. The research method used is qualitative descriptive analysis, focusing on the building's form, layout, and material usage. The findings indicate that the church continues to uphold the values of Tri Hita Karana, creating harmony between local culture and the church’s function as a place of worship. The application of this concept strengthens the local architectural identity in religious buildings, reflecting the cultural locality of Bali.